Evaluation of Broadly Neutralizing Antibody Sensitivity by Genotyping and Phenotyping for Qualifying Participants to HIV Clinical Trials. (1st September 2021) - Moldt, Brian; Parvangada, Aiyappa; Martin, Ross; Pace, Craig; Balakrishnan, Mini; Thomsen, Nathan D.; E. Collins, Sean; Kuster, Herbert; Braun, Dominique L.; Günthard, Huldrych F.; Geleziunas, Romas; Callebaut, Christian
Abstract : Background: HIV envelope (env) diversity represents a significant challenge for the use of broadly neutralizing antibodies (bNAbs) in HIV treatment and cure studies. Screening for viral sensitivity to bNAbs to select eligible trial participants will be important to improve clinical efficacy; however, no universal approach has been established. Methods: Pre-antiretroviral therapy plasma virus from participants in the Zurich Primary HIV Infection (ZPHI) study was genotyped and phenotyped for sensitivity to the bNAbs elipovimab (EVM, formerly GS-9722) and 3BNC117. The genotyping and phenotyping assessments were performed following the Clinical Laboratory Improvement Amendments of 1988 guidelines as required for entry into clinical trials. The genotypic-based prediction of bNAb sensitivity was based on HIV env amino acid signatures identified from a genotypic–phenotypic correlation algorithm using a subtype B database. Results: Genotyping the plasma virus and applying env sensitivity signatures, ZPHI study participants with viral sensitivity to EVM and 3BNC117 were identified. ZPHI study participants with virus sensitive to EVM and 3BNC117 were also identified by phenotyping the plasma virus. Comparison of the genotypic and phenotypic sensitivity assessments showed strong agreement between the 2 methodologies. Conclusions: The genotypic assessment was found to be as predictive as the direct measurement of bNAb sensitivity by phenotyping and may, therefore, be preferred because of more rapid turnaround time and assay simplicity. A significant number of the participants were predicted to have virus sensitive to EVM and 3BNC117 and could, thus, be potential participants for clinical trials involving these bNAbs. Abstract : Supplemental Digital Content is Available in the Text.